2011
DOI: 10.1634/theoncologist.2010-0361
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of the Dose of Cytarabine in the Upfront Treatment of Primary CNS Lymphomas with Methotrexate-Cytarabine Combination

Abstract: Background. The combination of high doses of methotrexate (MTX) and cytarabine (araC) is the standard chemotherapy for patients with primary CNS lymphoma (PCNSL). The addition of an alkylating agent could improve MTX-araC efficacy because it is active against quiescent G0 cells and increases antimetabolites cytotoxicity. A pilot experience with high doses of MTX, araC, and thiotepa (MAT regimen) was performed to investigate feasibility and efficacy of adding an alkylating agent. With respect to MTXaraC combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 10 publications
0
6
0
3
Order By: Relevance
“…A recent multi-centre phase II trial reported promising outcomes with 52 patients treated with R-MPV induction therapy followed by reduced or standard dose WBRT (23.4Gy (n = 31) or 45Gy) and cytarabine consolidation [ 10 •], achieving median PFS and OS of 3.3 and 6.6 years, respectively. The addition of thiotepa to HD-MTX and cytarabine was piloted in a small multi-centre study (n = 20), with inferior results compared to the IELSG20 trial, attributed to a 50 % protocol reduction in cytarabine dose (1 g/m 2 for four doses) [ 44 ], although the optimal thiotepa dose in this setting has not been ascertained. The role of thiotepa is currently being evaluated in the ongoing, randomised IELSG32 study (EudraCT number 2009-012432-32).…”
Section: Treatmentmentioning
confidence: 99%
“…A recent multi-centre phase II trial reported promising outcomes with 52 patients treated with R-MPV induction therapy followed by reduced or standard dose WBRT (23.4Gy (n = 31) or 45Gy) and cytarabine consolidation [ 10 •], achieving median PFS and OS of 3.3 and 6.6 years, respectively. The addition of thiotepa to HD-MTX and cytarabine was piloted in a small multi-centre study (n = 20), with inferior results compared to the IELSG20 trial, attributed to a 50 % protocol reduction in cytarabine dose (1 g/m 2 for four doses) [ 44 ], although the optimal thiotepa dose in this setting has not been ascertained. The role of thiotepa is currently being evaluated in the ongoing, randomised IELSG32 study (EudraCT number 2009-012432-32).…”
Section: Treatmentmentioning
confidence: 99%
“…40 A recent study highlighted the importance of ara-C dose, suggesting that 4 doses of 2 g/m 2 is an appropriate choice. 41 Although it was not addressed in a phase 3 trial, the MTX-ara-C combination is the current standard chemotherapeutic approach for de novo PCNSL as it is supported by the highest level of evidence available (Figure 4). …”
mentioning
confidence: 99%
“…This study used a relatively low dose of Ara‐C (1 g/m 2 × 4), in an effort to minimize the toxicity of the regime. More recently available data in PCNSL suggested worse outcomes in patients receiving 1 g/m 2 (treated outwith a clinical trial) compared to those who had received 2 g/m 2 in the International Extranodal Lymphoma Study Group trial (IELSG20) (Ferreri et al , , ). No direct comparison has been made, however.…”
Section: Discussionmentioning
confidence: 99%